2021
DOI: 10.1002/ijc.33832
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transport proteins are secreted by cancer cells and identified as potential novel cancer biomarkers

Abstract: Previous studies have identified increased expression of members of the nuclear transport protein family in cancer cells. Recently, certain nuclear transport proteins have been reported to be secreted by cells and found in the serum. The aims of our study were to investigate the levels of multiple nuclear transport proteins secreted from cancer cells, and to determine their potential as diagnostic markers for cervical and oesophageal cancer. Mass spectrometry identified 10 nuclear transport proteins in the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In other words, the miR-144-3p antagonist could rescue the knockdown effects of LNC EBLN3P, thereby allowing normal cell proliferation, which is indicative of their direct regulatory relationship. In addition, TNPO1 is identified as an oncogene and has been reported to be associated with the development of esophageal cancer and cervical cancer [9,26], consistent with our finding that TNPO1-knockdown inhibited proliferation of A549 cells. In our study, we reveal that the knockdown of LNC EBLN3P induced by carbon ion irradiation could inhibit cell proliferation and induce apoptosis and radiosensitivity of NSCLC cells through the down-regulation of TNPO1, demonstrating that TNPO1 may be a key factor functioning in the radiobiological effects of heavy ions.…”
Section: Discussionsupporting
confidence: 91%
“…In other words, the miR-144-3p antagonist could rescue the knockdown effects of LNC EBLN3P, thereby allowing normal cell proliferation, which is indicative of their direct regulatory relationship. In addition, TNPO1 is identified as an oncogene and has been reported to be associated with the development of esophageal cancer and cervical cancer [9,26], consistent with our finding that TNPO1-knockdown inhibited proliferation of A549 cells. In our study, we reveal that the knockdown of LNC EBLN3P induced by carbon ion irradiation could inhibit cell proliferation and induce apoptosis and radiosensitivity of NSCLC cells through the down-regulation of TNPO1, demonstrating that TNPO1 may be a key factor functioning in the radiobiological effects of heavy ions.…”
Section: Discussionsupporting
confidence: 91%
“…IPO5 is elevated in colorectal cancers and oesophageal cancer, and this has been associated with increased tumorigenicity and metastasis [ 98 , 99 ]. Elevated IPO5 levels in the serum of oesophageal and cervical cancer patients has been proposed as a cancer biomarker [ 100 ]. We had previously demonstrated that IPO5 transcript and protein are abundant in foetal germ cells [ 40 , 42 ], GCNIS, seminomas, and in TCam-2 cells [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the observed results from the EVs of cervical cancer and other different malignancies propose them as potential therapeutic or diagnostic targets for this cancer. Initially, their utility as biomarkers was suggested due to the detection of their protein content (KPNB1, CRM1, CAS, IPO5, and TNPO1) in the serum of patients with cervical cancer [ 69 ]. However, the evaluation of any EV molecule as a possible marker or therapeutic target will be random if it is unknown whether it is found to be modified in the EVs in this cancer.…”
Section: Discussionmentioning
confidence: 99%